2012
DOI: 10.1016/j.jtcvs.2012.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Aprotinin revisited

Abstract: In 2008, we saw the withdrawal of aprotinin from the US markets after preliminary results from a large, randomized clinical trial in Canada. This drug, a potent antifibrinolytic, was used primarily in complex and/or redo cardiac surgery as an adjunct to decrease postoperative bleeding and complications. The Canadian study raised questions previously brought up in similar studies-does aprotinin increase the risk of mortality and renal failure after cardiac surgery? Recently, a re-review of the Canadian data not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
0
12
0
1
Order By: Relevance
“…6,8 Rereview of the BART data has suggested flaws in the study as well as in the interpretation of the results. 9 Adding to the controversy surrounding the withdrawal of aprotinin, the authors of the BART rejected the results of the review conducted by Health Canada. 10 Nonetheless, aprotinin has been reintroduced into clinical practice in Europe and in Canada, albeit on a very limited scale at this time.…”
mentioning
confidence: 99%
“…6,8 Rereview of the BART data has suggested flaws in the study as well as in the interpretation of the results. 9 Adding to the controversy surrounding the withdrawal of aprotinin, the authors of the BART rejected the results of the review conducted by Health Canada. 10 Nonetheless, aprotinin has been reintroduced into clinical practice in Europe and in Canada, albeit on a very limited scale at this time.…”
mentioning
confidence: 99%
“…To correct disturbances of the fibrinolysis as well as imbalances of the other proteolytic processes the animal trypsin inhibitor aprotinin is used as a drug (Trasisol, Contrical, Gordox etc) [24,13,40]. The effectiveness of the aprotinin in the treatment of some diseases has been questioned recently because of it's substantial disadvantages [23,12]. Following consultation with the German Federal Institute for Drugs and Medical Devices, the U.S. Food and Drug Administration, Health Canada, and other health authorities, the producer of Trasilol -Bayer announced in 2007 that it has elected to temporarily suspend worldwide marketing of Trasylol® (aprotinin injection) until final results from the Canadian BARTtrial can be compiled, received and evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the apparent importance of the correction of imbalances of the proteolysis in pathology, in fact only the pancreatic trypsin inhibitor (aprotinin) is used more or less widely as a protease inhibitor drug (Trasisol, Contrical, Gordox etc) in the treatment of some diseases [24,13,40]. Being the animal protein aprotinin possesses substantial disadvantages [23,12] and attempts to develop new drug on the base of plant or recombinant proteins or peptidomimetics are undertaken [35,27]. SBTI is one of the candidates for such a role [34].…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Bayer, the maker of aprotinin, was allowed to market the drug again in Canada and the European Union in 2011.…”
Section: The History Of Aprotinin Research and Its Regulationmentioning
confidence: 99%
“…A Health Canada expert advisory panel and the European Medicines Agency stated that the BART and its primary report in the New England Journal of Medicine were flawed, and recent comments have supported that claim. 7,8 As authors of the BART, we are concerned about the approach and decision-making in the process used by Health Canada to arrive at its 2011 decision, and about the subsequent rulings of Health Canada and the European Medicines Agency. We refute the three primary criticisms of the BART, and we believe that patients are being put at substantial risk in the presence of safer alternatives.…”
mentioning
confidence: 99%